Telegram Implementation on Security and Monitoring of Home Door Keys Based on Wemos and Internet of Things - Bambang Kurniawan; Haris Tri Saputra (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Good home security will make homeowners feel comfortable leaving the house. The existing home door security system still has weaknesses in certain types, for example for door locks using Radio Frequency Identification (RFID), if the RFID card is damaged, it will be difficult to unlock the door. The absence of a door lock monitoring system is locked or not when the user leaves the house will also reduce the user's sense of security and comfort. This study aims to improve the security of door locks by utilizing bots on the Telegram application installed on Smartphones as door lock controls and can make it easier for users to monitor the state of house door locks from anywhere with the concept of the Internet of Things. The telegram bot is used to send commands to open or lock the house door to the WEMOS D1 Microcontroller which then becomes the Actuator control in the form of a Solenoid Door Lock with a Relay as a connector. Thus the integration of the microcontroller and the Telegram application with the IoT concept can be a door security solution. However, it does not rule out the possibility of a security hole in the system created.